Identification of Predictive Factors for Massive Transfusion Activation in Trauma Patients: A Systematic Review and Meta-analysis - Thosapol Ueamsaranworakul; Ratcharin Niamjumnong; Kumpol Kornthatchapong; Winchana Srivilaithon (Journal of Emergencies, Trauma and Shock)
Introduction: Acute blood loss and uncontrolled hemorrhage in trauma require quick identification and action to restore circulating volume and save the patient. These patients have the opportunity to receive massive transfusion (MT) to reduce mortality rates and avoid overtransfusion using a suitable ratio of blood components. This study aims to systematically review and analyze the predictive factors for the activation of MT protocol (MTP) in trauma patients, which is critical for improving clinical decision-making and patient outcomes. Methods: PubMed, ScienceDirect, Cochrane, and other sources were searched for articles from 2007 to 2020. Conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement, this systematic review included original studies published in English, involving trauma patients aged 15 years or older who received MTP. The risk of bias (RoB) was assessed using the RoB in Nonrandomized Studies of Interventions-I and RoB 2 tools, and statistical analysis was performed, focusing on the homogeneity of effect sizes across trials. Results: The articles search identified a total of 424 studies. Nine studies met all inclusion criteria. The most common predictors were age, sex, systolic blood pressure (SBP), heart rate (HR), hemoglobin (Hb) levels, international normalized ratio (INR), base excess (BE), and lactate levels. The analysis showed that parameters such as SBP, HR, Hb, INR, BE, and lactate were significantly associated with the activation of MTP. However, age and sex were not significant predictors. The survival rate was notably lower in the MTP group compared to the non-MTP group. There was no evidence of publication bias. Conclusion: Several physiological parameters: low SBP, elevated HR, reduced Hb, increased INR, diminished BE, and elevated lactate are significantly correlated with an increased likelihood of necessitating MTP in trauma patients. Among those who received MTP, the survival rate was lower compared to the non-MTP group.